1994
DOI: 10.22358/jafs/69817/1994
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the thermal processing on the protein value of double-low rapeseed products. 1. Effect of toasting temperature on protein value of rapeseed oil meal for pigs

Abstract: The effect of toasting process in the industrial conditions at 90,95, 100 (Plant 1) and 120°C (Plant 2) on protein value of a double-low rapeseed meal (RSM) for pigs was studied in two experiments. In Experiment 1, the ileal digestibility of RSM was evaluated, and in Experiment 2, the N balance and growth performance trial was carried out.It was found that raising of toasting temperature from 90 to 95 and 100°C in Plant 1 decreased the total and available lysine contents (5.20, 4.85, 4.33 and 4.28, 3.84, 3.00 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
(11 reference statements)
3
6
0
Order By: Relevance
“…These results confirmed findings obtained in the study by Grala et al (1994) who showed that increasing toasting temperature from 90 to 100°C markedly decreased protein value of RSM, especially the content of total and available lysine as well as the apparent ileal digestibility of protein and amino acids, N utilization and pig performance. In the present study the protein quality (TD, BV, NPU) and growth performance of rats (FC, BWG) decreased as lysine and available lysine contents in protein was reduced.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…These results confirmed findings obtained in the study by Grala et al (1994) who showed that increasing toasting temperature from 90 to 100°C markedly decreased protein value of RSM, especially the content of total and available lysine as well as the apparent ileal digestibility of protein and amino acids, N utilization and pig performance. In the present study the protein quality (TD, BV, NPU) and growth performance of rats (FC, BWG) decreased as lysine and available lysine contents in protein was reduced.…”
Section: Discussionsupporting
confidence: 91%
“…The protein value of seeds and cake was not directly dependent on total or available lysine concentrations in protein, in contrast to those samples which were heated (autoclaved) in the laboratory (Expt. 3) or to RSM toasted in the oil plant (Grala et al, 1994). Similarly to our study, other authors also showed that mild hydro-thermal treatment of double-low rape seeds increased their biological value (Slomiriski et al, 1985;Rakowska et al, 1987;Rotkiewicz, 1991).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations